High energy diet of beef cows during gestation promoted growth performance of calves by improving placental nutrients transport - Kang, Kun; Zeng, Lei; Ma, Jian; Shi, Liyuan; Hu, Rui; Zou, Huawei; Peng, Quanhui; Wang, Lizhi; Xue, Bai; Wang, Zhisheng (Frontiers in Veterinary Science, 2022)
The aim of this study was to explore the effects of dietary energy level during gestation on growth performance and serum parameters in offspring using beef cattle as research objects. Additionally, the gene expressions associated with nutrients transport in the placenta were evaluated. Eighteen Simmental crossbred cows (body weight = 338.44 ± 16.03 kg and 760 ± 6 d of age) were randomly assigned to 3 dietary treatment groups: low energy (LE, metabolic energy = 8.76 MJ/kg), medium (ME, 9.47 MJ/kg) and high (HE, 10.18 MJ/kg). The dietary treatments were introduced from day 45 before expected date of parturition. The pre-experiment lasted for 15 d and formal experiment lasted for 30 d. Growth performance data and blood samples of calves were collected at birth and day 30 post-birth. The placental tissue was collected at parturition. The results indicated that the birth weight and average daily gain of calves in HE group were higher (P < 0.05) than those in LE group. After parturition, the serum contents of glucose, total protein, cortisol and leptin in neonatal calves were significantly increased (P < 0.05) with the elevation of dietary energy levels. At 30 d postpartum, the glucose, glutathione peroxidase, growth hormone, insulin-like growth factor 1 and leptin concentrations of HE group were significantly increased (P < 0.05) as compared with LE group, while the serum amyloid protein A displayed an opposite trend between two groups. With the increase of dietary energy concentration, placental mRNA expressions of vascular endothelial growth factor A, glucose transporter 1 and 3 were significantly up-regulated (P < 0.05). Furthermore, the amino acid transporter solute carrier family 38 member 1, hydroxysteroid 11-beta dehydrogenase 2, insulin-like growth factor 1 and 2 mRNA expressions of HE group were higher (P < 0.05) than those of LE and ME groups. In conclusion, the improved growth performance of calves from the high energy ration supplemented beef cows may be attributed to the increased placental nutrients transport, which may lead to the increased nutrient supply to the fetus.